2019
DOI: 10.3390/coatings9070456
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Microbial Adhesion to Dental Materials by Roughness Parameters

Abstract: Microbial adhesion to intraoral biomaterials is associated with surface roughness. For the prevention of oral pathologies, smooth surfaces with little biofilm formation are required. Ideally, appropriate roughness parameters make microbial adhesion predictable. Although a multitude of parameters are available, surface roughness is commonly described by the arithmetical mean roughness value (Ra). The present study investigates whether Ra is the most appropriate roughness parameter in terms of prediction for mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…The role of polymer matrices on the overall antimicrobial activity of CNT/polymer composites can be attributed not only to the preservation of the inherent cytotoxicity of SWCNTs and MWCNTs ( Goodwin et al., 2015 ) but also to the promotion of the contact between CNTs and microorganism cell walls by reducing CNT autoaggregation ( Mohamed et al., 2019 ) ( Figure 4 ). Regarding the anti-adhesive effect of CNT/polymer composites, it seems to be strictly related with the uniform layer of polymer that surrounds the CNT surface and protect them from nonspecific protein adsorption, as well as with the CH-π interactions established between the polymer and the CNT surface ( Upadhyayula and Gadhamshetty, 2010 ; Beigbeder et al., 2008 ), and the topographic structure of the CNT/polymer composite surface (rough surfaces revealed to be more vulnerable to microbial adhesion than smooth surfaces) ( Kim et al., 2019 ; Schubert et al., 2019 ; Dantas et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The role of polymer matrices on the overall antimicrobial activity of CNT/polymer composites can be attributed not only to the preservation of the inherent cytotoxicity of SWCNTs and MWCNTs ( Goodwin et al., 2015 ) but also to the promotion of the contact between CNTs and microorganism cell walls by reducing CNT autoaggregation ( Mohamed et al., 2019 ) ( Figure 4 ). Regarding the anti-adhesive effect of CNT/polymer composites, it seems to be strictly related with the uniform layer of polymer that surrounds the CNT surface and protect them from nonspecific protein adsorption, as well as with the CH-π interactions established between the polymer and the CNT surface ( Upadhyayula and Gadhamshetty, 2010 ; Beigbeder et al., 2008 ), and the topographic structure of the CNT/polymer composite surface (rough surfaces revealed to be more vulnerable to microbial adhesion than smooth surfaces) ( Kim et al., 2019 ; Schubert et al., 2019 ; Dantas et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the weak bond, some of the large fillers might have detached from the matrix, resulting in concavity in the surface following toothbrushing abrasion, thereby increasing the surface roughness and decreasing the surface gloss [ 28 ]. Many studies concluded that toothbrushing significantly increases surface roughness [ 24 , 27 ] and any surface roughness above a threshold of 0.2 μm increases bacteria retention [ 29 ]. Therefore, the surface of a restoration is of considerable importance because it affects the function of a tooth through wear, abrasiveness, and build-up of plaque and calculus [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The desirable attributes of PMMA include low cost, high biocompatibility, and easy handling; consequently, it is commonly used in dentistry [ 2 ]. Dental appliances made of PMMA have direct contact with oral tissues, and because the oral cavity contains a variety of microorganisms, PMMA based appliances in the mouth are immediately covered by salivary components and colonized by a multitude of microorganisms that may form biofilms [ 3 ]. Biofilm formation on dental devices may cause dental caries, periodontal diseases, or inflammation of oral soft tissue [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%